General Botany - Fuller, Harry J.; Ritchie, Donald D. (New York : Barners & Noble Books, 1970)
General botany is designed as a supplementary text for courses in botany and general biology. It surveys the plant kingdom, describing the characteristics and evolution of its various members. This new edition contains up-to-date information on the structure and activities of plants, the nature of chromosomes, nucleic acids, protein formation, energy-transferring mechanisms, and timing mechanisms.
1. The Study of botany -- 2. The living state : plants and animals -- 3. The gross structure of seed plants -- 4. The microscopic structure of plants: cells and tissues -- 5. Relationship of plant cells to water -- 6. Roots and their relation to soils -- 7. The gross structure of stems -- 8. The internal structure of stems -- 9. The physiology of stems -- 10. The leaf : structure and physiology -- 11. Metabolism : digestion and respiration -- 12. Growth : cell division and differentiation -- 13. Growth : molecular action -- 14. Growth : environmental effects -- 15. Flower structure and activities -- 16. Fruits and seeds -- 17. Heredity and variation -- 18. The Classification of plants -- 19. Thallophyta : alagae -- 20. Thallophyta : fungi -- 21. Embryophyta : division bryophyta -- 22. Tracheophyta : psilipsida, lycopsida and sphenopsida -- 23. Tracheophyta : Pteropsida -- 24. Evolution -- 25. Plant ecology and geography -- 26. The Importance of plants in human life.
Includes bibliographical references and index.
Keywords: BOTANY